Effective Strategy of TOEFL Socialization for Students at SMK HKBP Pematangsiantar: Preparing Their Academic and Professional Future - Nainggolan, Lonatasya Sevari; Sihaloho, Damaris; Sinaga, Miranda; Simanjuntak, Yeni; Saragih, Ria Angelina; Sinaga, Yanti Kristina; Panjaitan, Muktar Bahruddin; Br Sinaga, Juli Antasari (Pengabdian Masyarakat Sumber Daya Unggul, 2024)
Community service (PKM) is an activity that provides knowledge and skills to the community. The aim of this socialization activity is to introduce and provide knowledge and insight to HKBP Pematangsiantar Vocational School students about the TOEFL test. On December 6, 2023, 23 class XI TKR-1 students took the TOEFL test. To carry out this socialization, there are three stages: preparation, implementation, and evaluation. The socialization material presented is about how to get to know Toefl, the purpose of Toefl, the use of Toefl, and displays several examples of Toefl questions. The students of Class In addition, this socialization can increase students' desire to learn English more seriously. The results of the implementation of the Test of English as Foreign Language (TOEFL) socialization provide participants with knowledge, understanding, and encouragement to take it. This shows how important the TOEFL is and how it should be administered to prepare students for their academic and professional futures.